Comparative Analysis of Clean Water Services in Tourism Area: Case Study of Singapore and Lembang, West Java - Enzelluthfiyah, Liza (International Journal of Sustainable Competitiveness on Tourism, 2026)
The tourism industry influenced by clean water, which impacts service quality, tourist health, and the environment. Clean water crises are occurring in various countries worldwide. The World Bank projects a 40% gap between clean water demand and supply by 2030. The purpose of this study is to analyze clean water management at tourism sites in Singapore and Lembang, West Java. Singapore is a developed country with an integrated system. Meanwhile, Lembang, West Java, is a tourism area that relies on natural resources. The research method is a comparative approach to clean water provision typology based on field surveys consisting of three tourism sites in Singapore: Fort Canning Park, Marina Bay Sands-Merlion Park, and Singapore Zoo. Thus, three tourism sites in Lembang, West Java, are Lawangwangi Creative Space, Floating Market Lembang, and Lembang Park and Zoo. Furthermore, the analysis used a SWOT approach. The results show that Singapore implements water storage and advanced technologies such as water recycling and desalination, supported by strict regulations and high efficiency. Meanwhile, clean water in Lembang comes from springs, private wells, and water subscriptions from the Drinking Water Company (PDAM). This analysis is crucial for uncovering the infrastructure and regulations between the two countries, thus providing an alternative source of clean water for other tourist destinations. This research is also expected to contribute to sustainable clean water management for the tourism sector, particularly within the context of the sustainable development goals (SDGs) on clean water and sanitation.